STUDY OF ELECTRICAL INSTALLATION PLANNING AT THE GENERAL HOSPITAL IN BENGKAYANG DISTRICT - Prabasa, Restu; Arsyad, M. Iqbal; Pontia W, F. Trias (Faculty of Engineering, Universitas Tanjungpura, 2023)
The Regional General Hospital of Bengkayang Regency is planning the construction of a new building. The Bengkayang Regency General Hospital building will be planned to total 2 buildings, namely the Central Medical building and the IRNA building, where the Central Medical building has 4 floors with an area of 8024.62 m2 and the IRNA building has 3 floors with an area of 5945.55 m2 and several rooms to be built include: INFECTIOUS, IGD, Obstetric Installation, ICU, ICCU, HCU, Operating Room, and IRNA Room. To build the Regional General Hospital of Bengkayang Regency, it is necessary to plan electrical installations which are part of the initial stage of work. In planning this electrical installation, the need for electrical energy to serve the load must be in accordance with the Indonesian National Standard which refers to the Regulation of the Minister of Health of the Republic of Indonesia Number 24 of 2016 concerning technical requirements for hospital buildings and infrastructure and the General Regulation of Electrical Installations (PUIL) 2011. Research on the planning of this installation uses literature study methods and discriminatory analytics. At the planning stage, several calculations were carried out, namely calculating the need for lighting illumination, air conditioning capacity, conducting cross-sectional area, safety current rating, as well as making line diagrams and calculating cost budget details (RAB). Based on calculations and analysis, the amount of power to meet all electricity load needs is 624322 Watt and the total cost of all work is Rp. 5,623,488,000.00.